Antibacterial Activity Test of Ashitaba Leaf Extract Ointment Formulation (Angelica Keiskei (miq) Koidz) against Staphylococcus epidermidis Bacteria - Luluk Aniqoh Meliana Putri; Devita Riafinola Andaririt (Universitas STRADA Indonesia, 2021)
Acne is a condition in which the pores of the skin are blocked, causing inflamed pus pockets. One of the factors causing acne is bacteria. Staphylococcus epidermidis bacteria are bacteria found in acne. The use of medicinal plants is an alternative as a treatment for diseases including diseases caused by bacterial infections. Ashitaba leaves (Angelica Keiskei (miq) Koidz) positively contain alkaloids, saponins, tannins and flavonoids which play a role as antibacterials. The purpose of this study was to determine the antibacterial activity of the formulation of ashitaba leaf extract ointment preparations against Staphylococcus epidermidis bacteria that cause acne, using the well diffusion test method. Observation of the inhibitory power was tested on ashitaba leaf extract and ashitaba leaf extract ointment preparations with extract concentrations of Formula I 10%, Formula II 15%, Formula 20%. The results of this study are that the formulation of ashitaba leaf extract ointment preparations can have inhibitory power against Staphylococcus epidermidis bacteria. The highest inhibition zone in Formula III with an extract concentration of 20% with an inhibition zone diameter value of 7.27 mm.